PENGARUH KONSENTRASI KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN JASA GO PUBLIC - Farah Margaretha; Asmara Dhonna (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2011)
The purpose of this research is to find out the influence of concentrated ownership of two largest shareholder on go public service company performance in Indonesian. In this research, the data are collected from 15 company which are listed at Jakarta Stock Exchange from 2001 until 2006 with purposive sampling method. This research uses multiple linear regression as the analysis method. The results find out that there is influence between concentrated ownership and company performance which uses Return On Asset as the measures. The result also show there is no influence between Growth Revenue Rate and Return On Asset. So, the best contribution for this this research is managers have to attention to this factor more carefully .